Improved Flame Retardancy of Bacterial Cellulose Fabrics Treated Using the Plant-Based Materials Banana Peel, Beet, and Spinach - Juneyoung Minn; Hyunjin Kim; Bum Hoon Lee; Hye Rim Kim (Journal of Natural Fibers)
This study identified plant-based materials for use as flame retardants in combination with bacterial cellulose (BC) and enhanced the flame retardancy of BC fabrics. Eight plant-based materials were screened via thermogravimetric analysis, and banana peel, beet, and spinach were selected as plant-based flame retardants. The chemical and physical structure analyses of BC samples treated with banana peel, beet, and spinach, respectively, revealed that the plant-based flame retardants were entrapped within the BC matrices without changing the structure of BC. The flame retardancy of the plant-based flame retardant-treated BC samples was compared to that of BC treated with the sodium metasilicate nonahydrate, which is a commercial flame retardant. Vertical flammability and char morphology studies confirmed that the plant-based flame retardant-treated BC samples formed honeycomb chars during combustion. The limiting oxygen indices of the plant-based flame retardant-treated BC samples were 40–47%, which exceeded that of sodium metasilicate nonahydrate-treated BC of 36%. In thermogravimetric analysis, the residual masses of the plant-based flame retardant-treated BC samples were similar to that of sodium metasilicate nonahydrate-treated BC. Therefore, BC fabrics with improved flame retardancy were developed using plant-based flame retardants.